The Effect of Community Empowerment Program for Fisherman Community to Enhance the Market Penetration a Case Studies in Tuban Indonesia - W., Muslichah Erma; Retnowati, Nova; Soeharjoepri, Soeharjoepri (Archives of Business Research, 2018)
This study is an action research study in the form of community empowerment program. The study aim to help the fisherman community to growth in two aspect one is the production line and second is enhance the market penetration. The market penetration is required to increase the profit and minimalist the loss due to unsold product. The program is done in Tuban a district in East Java located in Indonesia. The program is done in many aspect from production standard procedures until the marketing management and branding process. The result of this study is shown that the increase of quality of production and also minimalist the time required, furthermore the result also shown the increase of market penetration through branding technique.